Vinicius de Moraes e Shelley: um exercício de desleitura . - Aquino, Adriana Assis de (2008)
Using Harold Bloom s methodology known as dialectical revisionism we undertake the task of misreading of Vinícius de Moraes (1913- 1980) poems Poética (1950), Operário em construção (1955), Poética II (1960) against Percy Bysshe Shelley (1792-1822) and his poem A Song: Men of England, suggesting that the Brazilian poet trammeled a battle with his poetic triad, in which Operário em Construção is Vinicius s main weapon. It is suggested here that each one of Vinícius´poem represents a step of what Bloom calls anxiety of influence . The misreading proposed confronts the themes and the imagery of the poems, arguing that Shelley and Vinícius are similar when they approach exploitation and working class consciousness according to the Dialectic Marxism pattern, and that Vinícius´s poem was not only inspired by Shelley s, but using one of the strategies suggested by Bloom, he corrects the ideological flaws of Shelley s poem. It is also discussed the possibility that both poems are inspired by Plato´s (428-7 a 348-7 a.C.) allegory of the cave, his concept of justice and the moral construction of the polis defended in A República. Thus, considering the process of misreading, these five poems constitute what Bloom calls a family romance , which is characterizes the phenomenon of melancholy of creativity